Downy Mildew Disease of Pearl Millet (Bajra): Infection, Damage and Management Strategies - Sudhakar, R.; Reddy, P. Narayana; Bharathi, V. (International Journal of Bio-resource and Stress Management, 2023)
Systemic symptoms downy mildew disease of pearl millet (Pennisetum glaucum L.) generally appear on the second leaf, subsequently leaves and panicles also develop symptoms. Leaf symptoms begin as chlorosis (yellowing) at the base of the leaf lamina, and successively higher leaves show a progression of greater leaf coverage. Inoculation of plants by spraying with a suspension of zoospores (released from sporangia of Sclerospora graminicola) induced immediate encystment of the zoospores and drastically reduced their ability to cause disease. The earliest symptom expression and the highest downy mildew were recorded when oosporic powder was placed below and above the seeds in furrows. Genetic resistance is the most economic and feasible method for control. Cuticular and epidermal thickness were significantly higher in leaves of the highly resistant cultivar (P-310-17) compared with the highly susceptible cultivar (7042 DMS). Seed treatment with 6 g Apron 35 WS kg-1 of seed + spray of 4 g Ridomil MZ l-1 recorded the lowest disease incidence at 30 days after sowing and at the dough stage.